Kohesi Gramatikal Dan Kohesi Leksikal Pada Novel Hidup Tak Selalu Baik-Baik Saja Karya Zee Zee Aurora - wati, Rahayu Listyo; Sabardila, Atiqa (JURNAL PENDIDIKAN ROKANIA, 2024)
This research aims to analyze grammatical and lexical cohesion in the novel Life is Not Always Fine by Zee Zee Aurora. Grammatical and lexical cohesion are important aspects in maintaining the integrity of the text, resulting in a story line that is more coherent and easy for readers to understand. This research uses a qualitative descriptive method with a text analysis approach, where data is taken from various chapters in the novel. Data were analyzed based on the theory of grammatical cohesion which includes reference, substitution, ellipsis and conjunction, as well as lexical cohesion which includes repetition, synonymy, antonymy and collocation. Apart from that, this research also uses data collection carried out through documentation techniques. The research results show that this novel uses grammatical cohesion predominantly in references and conjunctions, while in lexical cohesion, repetition and synonymy are most often used. This use of grammatical and lexical cohesion contributes to an orderly storyline and strengthens the emotional meaning and themes in the novel. It is hoped that this research can provide new insights into the linguistic study of literary texts and become a reference for writers in improving the quality of text integration in literary works.`